"Music for Affect Regulation": music listening in group receptive music therapy in the treatment of depression. Issue 1 (1st June 2016) - Laansma, Meertine M.J.; Haffmans, P.M. Judith
Abstract : In this paper an experimental multiple case design ( N  = 8) study will be presented on the effect of music listening to preferred music in receptive music therapy in the treatment of chronic depression with outpatients. Background : Depression causes problems in the recognition and experience of emotions. Music listening seems to be effective in experiencing emotions and regulate mood and is linked to emotional processing, which helps patients to recognize, tolerate and regulate emotions. Objective : The aim of this study was to investigate which affect regulation strategies are used by depressive patients while listening to music in music therapy for regulating their mood. Method : An exploratory study was performed with outpatients in a part-time group in a day treatment programme. Experienced emotions and strategies were measured after listening by two self-report questionnaires and underlying mechanisms were queried in the sessions. Discussion/conclusion : The results suggest that music listening is an effective intervention for identifying and intensifying experienced emotions and regulation strategies. Significant correlations between strategies and regulated emotions gave insight into the components of affect regulation strategies.